Art entrepreneurship: Solutions for those grieving the loss of a family breadwinner - Susana Prapunoto; Christiana Hari Soetjinighsih; Karyna Dewi Santoso; Andre Novan Andika; Indrianto; Lidia Natalia (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang)
Grief affects many elements of life, including psychological, spiritual, social, and economic ones. It can affect anyone, especially if the deceased was the main provider for a family that was not as rich. The art entrepreneurship intervention at GKJ Kartasura aims to give those who have been left behind by their family's primary provider a financial and psychological cure. Data was gathered using the Adult Attitude to Grief scale. Feelings of empowerment, resilience, and loss of control are the three domains that are measured. Individual measurements were taken both before and after the workout. To supplement the information gathered from the training participants, participant observations and in-depth interviews were also employed. The training was customized for each individual based on their skills and interests. 14 people showed up for the program, depending on how committed they were. The results indicate a reduction in grief and an improvement in participants' well-being following involvement in art entrepreneurship activities. Beyond economic benefits, the program fostered enthusiasm, hope, mental resilience, and self-confidence. Furthermore, it created new employment opportunities through the production and promotion of artistic works.